Clinical Profile and Endoscopic Management in Patients with Choledocholithiasis - Lamsal, Manoj; Jha, Anurag; Kafle, Brindeswari; Hamal, Rabin; Sherpa, Tshering Wangdi; Kafle, Pradip Kumar; Bhattarai, Tulsi Ram; Bhusal, Mohan; Koirala, Dinesh; Pathak, Rahul (Journal of Nepal Health Research Council, 2024)
Background: Common bile duct stones is a common medical problem that are usually seen in association with gallstone disease. Endoscopic management of Common bile duct stones involves doing Endoscopic retrograde cholangiography for bile duct clearance which is the primary therapeutic modality of choice. This prospective study was done to identify the clinical characteristics and outcome of patients presenting with Common bile duct stones undergoing Endoscopic retrograde cholangiography. Methods: A prospective observational study was conducted on all patients undergoing Endoscopic retrograde cholangiography in department of Gastroenterology, Tribhuvan University Teaching Hospital, for management of diagnosed or suspected choledocholithiasis from April 2023 to March 2024. Patient demographics, clinical characteristics, Endoscopic retrograde cholangiography findings and post procedure outcome data were collected and analysed. Results: A total of 110 patients (61.8% male and 38.2% female) were included in the final analysis. Successful clearance of Common bile duct was obtained in 76.4% patients with overall adverse events of 18% related to the procedure. Among patients undergoing the procedure, 16.4% couldn’t be managed with Endoscopic retrograde cholangiography and were referred for surgical management. Conclusions: Endoscopic management in form of Endoscopic retrograde cholangiography is a safe and effective method to manage patients with Common bile duct stones. Keywords: Common bile duct calculi; endoscopic sphincterotomy; ERCP.